Implementasi Penyaluran Zakat Oleh Badan Amil Zakat Nasional Kota Jambi Kepada Korban Pinjaman Online - Syelvita, Rema; Amin Qodri, Muhammad; Alissa, Evalina (Universitas Jambi, Fakultas Hukum, 2024)
This study aims to explore the role of the National Amil Zakat Agency (BAZNAS) of Jambi City in assisting individuals burdened with debt, including those who have fallen victim to online loans. Although the phenomenon of online loans has caused many people to face financial difficulties due to high interest rates and inhumane collection practices, the findings of this study show that, to date, no one has directly sought assistance from BAZNAS Jambi City as a result of being a victim of online loans. Generally, those seeking assistance from BAZNAS are individuals in debt to meet basic needs or cover medical expenses, with between one and five people receiving help each year. First, BAZNAS performs an identification step to make sure that the debt was used for legitimate purposes. Priority is given to impoverished individuals who are in genuine need. Through a descriptive qualitative approach and case studies in Jambi City, this research examines the effectiveness of zakat distribution by BAZNAS in assisting indebted individuals. The findings indicate that while zakat can alleviate financial burdens, its effectiveness needs to be enhanced through broader public education and more accurate identification mechanisms to reach more victims of online loans and others in financial distress.